2011
DOI: 10.2478/v10181-011-0050-7
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mammalian species, generated by somatic cell cloning, in biomedicine, biopharmaceutical industry and human nutrition/dietetics - recent achievements

Abstract: Somatic cell cloning technology in mammals promotes the multiplication of productively-valuable genetically engineered individuals, and consequently allows also for standardization of transgenic farm animal-derived products, which, in the context of market requirements, will have growing significance. Gene farming is one of the most promising areas in modern biotechnology. The use of live bioreactors for the expression of human genes in the lactating mammary gland of transgenic animals seems to be the most cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…But, the low cloning efficiency and reconstructed embryo dysplasia resulting from incomplete reprogramming of the donor nucleus are responsible for the slow pace of development in the field of porcine SCNT (Hill et al 2000;Yang et al 2007). Different studies have shown that the most important and effective way to promote epigenetic reprogramming of donor cell nuclei and restore their totipotency is to change the histone acetylation or DNA methylation status of somatic cell genome before and/or after its transplantation into a cytoplasm of enucleated recipient oocyte (Samiec et al 2012;Staszkiewicz et al 2013;Zhou et al 2014;Samiec et al 2015). Alone treatment of donor cells with different concentrations of FK228 for 24 h did not obviously improve the cleavage rate of cloned embryos.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But, the low cloning efficiency and reconstructed embryo dysplasia resulting from incomplete reprogramming of the donor nucleus are responsible for the slow pace of development in the field of porcine SCNT (Hill et al 2000;Yang et al 2007). Different studies have shown that the most important and effective way to promote epigenetic reprogramming of donor cell nuclei and restore their totipotency is to change the histone acetylation or DNA methylation status of somatic cell genome before and/or after its transplantation into a cytoplasm of enucleated recipient oocyte (Samiec et al 2012;Staszkiewicz et al 2013;Zhou et al 2014;Samiec et al 2015). Alone treatment of donor cells with different concentrations of FK228 for 24 h did not obviously improve the cleavage rate of cloned embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic cell nuclear transfer (SCNT) is of profound significance to save endangered animals, create transgenic animals, duplicate elite livestock, and provide tools and materials for basic research in biomedical field (Sameic 2005;Samiec & Skrzyszowska 2011a, 2011b. Transgenic cloned pigs are of great importance in animal husbandry and are also regarded as an ideal model for human diseases due to these characteristics of abundant resources, high fecundity, and physiological and anatomical structure similarities to humans (Samiec & Skrzyszowska 2011a;Samiec et al 2012;Kurome et al 2013;Ma et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hallmark of the pluripotency of embryonic stem (ES) cells and induced pluripotent stem (iPS) cells was demonstrated by the observation that their subclonal cultures are distributed into all embryonic tissues including germ cells when reintroduced into other host embryos . In addition to the investigation of embryo pluripotency characteristics, chimeric embryos are also valuable in studies focused on embryogenesis and fetogenesis and in transgenic research . However, reports on porcine chimeras were rare.…”
mentioning
confidence: 99%
“…The results show that chimeric pigs can be produced by aggregating cloned embryos and that the developmental capability of the cloned embryo in the subsequent chimeric development could be affected by the growth characteristics of its donor cell.A hallmark of the pluripotency of embryonic stem (ES) cells and induced pluripotent stem (iPS) cells was demonstrated by the observation that their subclonal cultures are distributed into all embryonic tissues including germ cells when reintroduced into other host embryos [1,2]. In addition to the investigation of embryo pluripotency characteristics, chimeric embryos are also valuable in studies focused on embryogenesis and fetogenesis [3][4][5] and in transgenic research [4,[6][7][8]. However, reports on porcine chimeras were rare.…”
mentioning
confidence: 99%